Audit reform: impact on markets - Matos, Beatriz Alexandre de (2019)
This Work Project will analyse the new Regulation issued about key matters of audit and also its impacts in the market. The key points being analysed are the mandatory rotation of audit firms and partners and the limitation of non-audit services. These will be studied through the vision of several agents of the markets. It will be briefly studied the impacts of this Regulation in Portugal (in terms of audit firms, fees, qualifications). This Regulation will solve some problems, such as the independence of the auditor, however there is not enough evidence that costs are being outweighed by the advantages.